Major sources of moisture for Antarctic ice-core sites identified through a Lagrangian approach - Nieto Muñiz, Raquel Olalla (2010)
A Lagrangian method of diagnosis was used to identify the major sources of moisture for principal Antarctic ice-core sites by back-tracking the air masses that ultimately reach these regions for a 5 yr period (2000–2004). This method, making use of the FLEXPART model, allowed quantification of moisture sources with better horizontal and vertical resolution than has previously been achieved. FLEXPART computes every 6 h with a 1° × 1° resolution and all 60 vertical levels of the European Centre for Medium-Range Weather Forecasts operational analysis. Our results confirm the previous identification of the sources of moisture in the Antarctic in relation to their subtropical origin, the region of major moisture contribution being centred on 40° S in a latitude band ranging between 30 and 50° S.